The growth-promoting role of the intestinal microbiota in Opsariichthys bidens: implications for selective breeding - Zeng, Gaoxiong; Liao, Mengxiang; Weng, Manxin; Hu, Zhenhui; Hu, Zhenxi; Chen, Duhuang; Fan, Haiping; Gao, Yu; Zhang, Yifan; Naz, Misbah; Dai, Zhicong; Xue, Lingzhan; et al. (Frontiers in Marine Science, 2025)
Differences in growth rates are commonly observed within cultured populations of the Opsariichthys bidens. In this study, we investigated the role of the intestinal microbiota in the growth and development of O. bidens by comparing two populations from a full-sib family: one with rapid growth (the OW group) and another with slow growth (the UW group). The intestinal contents were analyzed using 16S rRNA sequencing, and histological staining was used to observe intestinal morphology. Digestive enzyme activities and gene expression related to growth and metabolism were also examined. The OW group was dominated by Burkholderia-caballeronia-Paraburkholderia species, and Cetobacterium dominated the UW group. The development of villi and digestive enzyme activities in the OW group were greater than those in the UW group. Transcriptome analysis indicated elevated expression of anabolic genes in the OW group. The correlations coefficients between intestinal microbiota and indicators such as the growth phenotype, intestinal morphological structure, digestive enzyme activity, and gene transcription in O. bidens were all positive. This study investigated the correlation between the intestinal microbiota of O. bidens and various growth indicators, offering guidance and practical applications for the selection and breeding of fast-growing aquaculture varieties.